Future Trends in Biotechnology - Zhong, Jian-Jiang.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Systems Metabolic Engineering: The Creation of Microbial Cell Factories by Rational Metabolic Design and Evolution, by Chikara Furusawa, Takaaki Horinouchi, Takashi Hirasawa, Hiroshi Shimizu Impacts of Quorum Sensing on Microbial Metabolism and Human Health, by Yang-Chun Yong, Jian-Jiang Zhong CHO Glycosylation Mutants as Potential Host Cells to Produce Therapeutic Proteins with Enhanced Efficacy, by Peiqing Zhang, Kah Fai Chan, Ryan Haryadi, Muriel Bardor, Zhiwei Song Cell-Free Biosystems for Biomanufacturing, by Chun You, Y.-H. Percival Zhang Lipid Bilayer Membrane Arrays: Fabrication and Applications, by Xiaojun Han, Guodong Qi, Xingtao Xu, Lei Wang RNA Aptamers: A Review of Recent Trends and Applications, by Kyung-Nam Kang, Yoon-Sik Lee
Systems Metabolic Engineering: The Creation of Microbial Cell Factories by Rational Metabolic Design and Evolution, by Chikara Furusawa, Takaaki Horinouchi, Takashi Hirasawa, Hiroshi Shimizu -- Impacts of Quorum Sensing on Microbial Metabolism and Human Health, by Yang-Chun Yong, Jian-Jiang Zhong -- CHO Glycosylation Mutants as Potential Host Cells to Produce Therapeutic Proteins with Enhanced Efficacy, by Peiqing Zhang, Kah Fai Chan, Ryan Haryadi, Muriel Bardor, Zhiwei Song -- Cell-Free Biosystems for Biomanufacturing, by Chun You, Y.-H. Percival Zhang -- Lipid Bilayer Membrane Arrays: Fabrication and Applications, by Xiaojun Han, Guodong Qi, Xingtao Xu, Lei Wang -- RNA Aptamers: A Review of Recent Trends and Applications, by Kyung-Nam Kang, Yoon-Sik Lee.
Keywords: Chemistry; Biotechnology; Cytology; Biomedical engineering; Chemistry; Biotechnology; Cell Biology; Biomedical Engineering